SMEs Internal Determinants and its Sustainability Performance Among SMEs in Akwa Ibom State and Lagos State, Nigeria - Chigbu, Christian Chisom; r Imma Yazreen, Binti MD Yusoff; Noriza, Jaafar; Arshad, Ayub (HRMARS, 2023)
The study aims to examine SMEs internal determinants and its’ sustainability performance in Akwa Ibom State and Lagos State, Nigeria. The study’s philosophy centres on quantitative, questionnaires were adopted and 650 questionnaires were distributed for self-completion, and 600 were completed and returned. Both SPSS and SmartPLS were adopted for descriptive statistic, path regression and hypotheses testing. The study outcome posits that founder entrepreneurial leadership attribute have strongly correlated with economic sustainability, internal and external social sustainability performance and environmental sustainability performance. Founder’s entrepreneurial human capital showed a positive significant interrelation with internal social sustainability performance and environmental sustainability performance, whereas insignificant relationship with economic sustainability performance and external social sustainability performance. Founder’s entrepreneurial social capital showed a strong interconnection with economic sustainability performance; external social sustainability performance and environmental sustainability performance, and negatively related to internal social sustainability performance. The study’s contributed to existing knowledge and managerial implications, limitations, and future direction and study are described.